The Influence Of Korean Wave Brand Ambassadors, Brand Image And Brand Awareness On The Purchase Decision Of Somethinc Products (Survey on Somethinc Product Consumers in Tasikmalaya City) - Afiani, Dini Nurrizky; Pauzy, Depy Muhamad; Risana, Dudu (Universitas Dehasen Bengkulu, 2024)
Currently, competition among companies in the beauty industry is increasing rapidly. In the midst of intense competition, Somethinc tries to implement various appropriate marketing strategies to attract consumer buying interest, one of which is utilizing the Korean Wave phenomenon by appointing NCT Dream and Han So Hee as Brand Ambassadors. In addition to the Korean Wave Brand Ambassador variable, the Brand Image variable and the Brand Awareness variable will be measured in this study. The purpose of this study is to determine the effect of Korean Wave Brand Ambassadors, Brand Image and Brand Awareness on Purchase Decision of Somethinc Products in Tasikmalaya City. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Somethinc Products. The types of data used are primary data and secondary data. The data analysis technique used is multiple linear regression analysis. The results of this test prove that the Korean Wave Brand Ambassador, Brand Image and Brand Awareness have a significant effect both simultaneously and partially on the Purchase Decision of Somethinc Products in Tasikmalaya City.